Ethnographic Analysis to Identify Customer Experience and Customer Behavior in The Food and Beverage Industry - Efti Novita Sari; Anita Bawaiqki Wandanaya; Dominica Maria Ratna Tungga Dewa; Didit Hadayanti; Iwan Henri Kusnadi (Jurnal Sistim Informasi dan Teknologi, 2024)
This research aims to understand and describe the behavior of a group of people who consume craft beverages. We will conduct this research using a type of ethnography known as particularistic ethnography. We will use qualitative research techniques like group meetings and in-depth interviews in this research. In the analysis of men's mind maps, the words friends and food appeared most frequently, indicating that men associate drinking craft beverages with strong relationships with friends and consume them in a relaxed and informal setting, often accompanied by food consumption. On the other hand, in the analysis of women's mind maps, although the compartments are similar to men's with the dominance of the word friend, the difference lies in the consistent use of pink in writing words, especially friendship. This suggests that women associate craft beverages with camaraderie with friends in a fun, relaxed atmosphere. Both men and women equated craft beverages with femininity. They describe these characteristics as being informal, wearing jeans, having a friendly attitude, and having positive energy. This suggests that craft beverage typically evokes an informal and relaxed atmosphere, lacking the structure of other products or services. This shows that consumers see craft beverages as fun, warm, and suitable for enjoying in a relaxed, friendly atmosphere. Craft beverages and social interactions between friends have a strong connection, and drinking craft beverages occurs in a relaxed and laughter-filled atmosphere.